The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2000
DOI: 10.1038/sj.onc.1203743
|View full text |Cite
|
Sign up to set email alerts
|

pRb and Cdk regulation by N-(4-hydroxyphenyl)retinamide

Abstract: The cancer chemopreventive synthetic retinoid N-(4-hydroxyphenyl)retinamide (HPR) can inhibit the growth and induce apoptosis of tumor cells. In this study we analysed the growth suppressive e ect of HPR on human breast cancer cell lines in vitro and the role of the retinoblastoma protein (pRb) in this response. Treatment of MCF7, T47D and SKBR3 for 24 ± 48 h with 3 mM HPR, a concentration attainable in vivo, resulted in growth inhibition and marked dephosphorylation of pRb involving Ser 612 , Thr 821 , Ser 79… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 40 publications
(65 reference statements)
1
19
1
Order By: Relevance
“…It has been reported that 4-HPR and 4OH-Tam downmodulate transcription of Cyclin D1 (Panigone et al, 2000). Therefore, it is possible that the expression of Cyclin D1 from a heterologous promoter that is not subjected to the repression by these drugs may render the rhabdoid cells less susceptible for the drug-mediated cytotoxicity.…”
Section: Expression Of Cyclin D1 From a Heterologous Promoter Rendersmentioning
confidence: 99%
“…It has been reported that 4-HPR and 4OH-Tam downmodulate transcription of Cyclin D1 (Panigone et al, 2000). Therefore, it is possible that the expression of Cyclin D1 from a heterologous promoter that is not subjected to the repression by these drugs may render the rhabdoid cells less susceptible for the drug-mediated cytotoxicity.…”
Section: Expression Of Cyclin D1 From a Heterologous Promoter Rendersmentioning
confidence: 99%
“…Treatment with 4-HPR exerts restrictions on the cell cycle regulating cyclin dependent kinase (CDK) pathway [12] and phosphorylation of retinoblastoma protein (pRb), whose dephosphorylation results in cell cycle arrest. Inhibition of cell cycle check points would prolong the duration of cell cycle arrest, contributing to cytokine mediated activation of intrinsic apoptotic pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Current experimental data suggest that fenretinide induces inhibitory effects by both receptor-dependent and -independent mechanisms (Sheikh et al 1995, Fanjul et al 1996, Sun et al 1999. These mechanisms include both an increase in the expression of RAR-b and a decrease in the expression of cell cycle modulators, such as cyclin D and cyclin-dependent kinases, in different cancer cell lines, including breast cancer cells (Liu et al 1998, Panigone et al 2000.…”
Section: The Synthetic Retinoid Fenretinidementioning
confidence: 99%